2014
DOI: 10.1590/s2175-78602014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Piperaceae do Parque Nacional do Viruá, Caracaraí, Roraima, Brasil

Abstract: ResumoPiperaceae possui cinco gêneros, aproximadamente 3.600 espécies com distribuição pantropical, e no Brasil a família está representada por cerca de 450 táxons. Portanto, o objetivo desta pesquisa foi realizar o estudo taxonômico das espécies que ocorrem no Parque Nacional do Viruá, estado de Roraima. AbstractPiperaceae comprises five genera, approximately 3.600 species with a pantropical distribution, and in Brazil this family is represented by about 450 taxa. Therefore, the aim of this research was do t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Piper genus constitutes one major class of medicinal plants used to manage pain and inflammatory disorders in folkloric practice and all genera are represented in the neotropical region, except the monotypic genus Zippelia, which is found in tropical Asia. In Brazil, Piperaceae is represented by about 450 taxa distributed in three genera; most are in both Atlântica and Amazon Forests, where approximately 280 and 230 taxa, respectively, can be found [14]. Its representatives may be epiphyte, terrestrial or rupicolous herbs, hemiepiphyte, vines, erect or scandent shrubs or small trees.…”
Section: The Piper Genusmentioning
confidence: 99%
“…Piper genus constitutes one major class of medicinal plants used to manage pain and inflammatory disorders in folkloric practice and all genera are represented in the neotropical region, except the monotypic genus Zippelia, which is found in tropical Asia. In Brazil, Piperaceae is represented by about 450 taxa distributed in three genera; most are in both Atlântica and Amazon Forests, where approximately 280 and 230 taxa, respectively, can be found [14]. Its representatives may be epiphyte, terrestrial or rupicolous herbs, hemiepiphyte, vines, erect or scandent shrubs or small trees.…”
Section: The Piper Genusmentioning
confidence: 99%
“…Piper demeraranum, illustrated in relatively recent studies (Steyermark 1984;Steyermark & Callejas 2003;Melo et al 2014), is characterized by the presence of pilose-pubescent trichomes in the branches and veins of the abaxial surface of the leaves, erect or retrorse in the branches, with oblong to elliptic-obovate leaves, asymmetrically cordate-auriculate at base, erect spikes with floral bract narrow-lunate to triangular, slightly winged and by oblong, densely pilose-puberulent fruits. It occurs in the Guianas, Venezuela (Steyermark & Callejas 2003), Colombia (Lleras & Cruz 2005), Ecuador (Callejas & Burger 1999), Peru (Brako et al 2003), Bolivia (Callejas et al 2015) and Brazil, in Acre, Amazonas, Pará, Rondônia, Roraima and Mato Grosso states (Flora do Brasil 2020).…”
Section: 11mentioning
confidence: 99%
“…The spikes have been described as erect, with 0.5-2.7 cm long and 0.2-0.6 cm thick, sustained by a peduncle up to 1 cm long, pubescent; the rachis are glabrous, the floral bract triangular, subpeltate, equally short-fringed throughout the margin and the fruits are glabrous, globoseellipsoidal, ca. 2 mm long, slightly pointed at apex and with 3 sessile stigmas (Yuncker 1973;Melo et al 2014). It occurs only in Brazil, in the states of Amazonas and Roraima (Flora do Brasil 2020), to where the distribution was recently expanded by Melo et al (2014).…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs from Mexico to South America (Steyermark & Callejas-Posada 2003), and in Brazil is present in the Atlantic and Amazon Forests, in the States of Roraima, Amazonas, Pará and Acre (Melo et al 2014, Guimarães et al 2015. In the study area, it was found in lowland, montane and alluvial (várzea) forests.…”
Section: Figures 4g-hmentioning
confidence: 99%